Sperm specificity and potential paternal effects in gynogenesis in the Amazon Molly (Poecilia formosa) - Cerepaka,Clarissa; Schlupp,Ingo (PeerJ, 2023)
The Amazon Molly (Poecilia formosa) reproduces by gynogenesis, a relatively rare form of asexual reproduction where sperm is required to trigger embryogenesis, but male genes are not incorporated into the genome of the embryo. Studying gynogenesis could isolate paternal non-genetic effects on reproduction. This study explored which of eleven related species can produce sperm to trigger gynogenesis through natural mating in P. formosa, and whether sympatry affects reproductive success in P. formosa. Reproductive outcomes measured were relative reproductive output (number of offspring in the first brood divided by female standard length), relative embryo output (number of embryos in the first brood divided by female standard length) and combined relative reproductive output (sum of relative reproductive output and relative embryo output). For large (>4 cm) P. formosa, combined relative reproductive output was higher with sympatric Atlantic Molly (Poecilia mexicana) males than with allopatric P. mexicana males. P. formosa produced live offspring or late-stage embryos with all species tested in the genera Poecilia and Limia but did not produce offspring or embryos with males from the genera Gambusia, Girardinus, Heterandria, Poeciliopsis, or Xiphophorus. This information, as well as the limitations characterized in this study, will set a foundation for use of P. formosa as a model for paternal effects and the species specificity of sperm on fertilization, embryogenesis, and reproductive success.
Keywords: Amazon Molly; Gynogenesis; Hybridization; Paternal effects; Poecilia formosa; Sperm specificity